(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the phenomenon of semantic confusion observed in conjunctions with relative clauses, occurrence of syncretic sign in clauses and the types of clauses with relative clauses according to this sign are analyzed. Systematic study of compound sentences, which are the syntactic unit of the language, conveying their meaning and importance to the future generation is becoming more important than ever. The subject of compound sentences is one of the problems that has been attracting the attention of Uzbek linguists for many years. It should be noted that even though this topic is one of the widely studied areas of linguistics, these problems cannot be said to have been fully resolved yet. Also, according to the sign of semantic confusion (syncretic) conjunctions with adverbial clauses, the appearance of syncretic meaningful relations in them with different grammatical means, and the study of the semantic and structural features of clauses with substantively mixed adverbial clauses, these clauses description of the type on the basis of a syncretic sign, at the same time, scientific views and conclusions are given on the discovery of new aspects within the scope of this problem by determining the linguistic factors of the study of linguistic issues specific to conjunctions with adverbial clauses in different aspects.